BAS/BSCR25 Importance of interaction between peroxisome proliferator-activated receptor-α and NADPH oxidases in cardiac hypertrophy. Issue 17 (26th August 2010) - Robinson, E; Grieve, D J
Abstract : Peroxisome proliferator-activated receptor-α (PPAR-α) and NADPH oxidases are known individually to have essential roles in left ventricular hypertrophy (LVH). However, the potential importance of interaction between the two in overall regulation of the hypertrophic phenotype is unclear. Here Nox2−/−, PPAR-α−/− and matched wild-type (WT) mice (n=8) underwent thoracic aortic constriction (TAC) or sham surgery and were studied 7 days later. No differences in basal contractile function (echocardiography) or LVH were observed. However, increased mRNA expression (real-time RT-PCR) of PPAR-α in Nox2−/− (1.49%±0.08 vs WT, 1.04%±0.11 arbitrary units; p<0.05) and of Nox2 in PPAR-α−/− mice (3.61%±1.21 vs WT, 0.95%±0.12 arbitrary units; p<0.05), together with increases in NADPH oxidase activity (lucigenin-enhanced chemiluminescence: PPAR-α−/−, 6.81%±0.94 vs WT, 3.49%±0.35 RLU; p<0.05), indicated co-regulation of myocardial Nox2/PPAR-α. As expected, TAC-induced LVH was significantly increased in PPAR-α−/− versus WT mice, but similar in Nox2−/− mice. Decreases in fractional shortening in WT mice (−16%±3%) were augmented in PPAR-α−/− and attenuated in Nox2−/− mice after TAC (−28%±4 and −10%±3; p<0.05 vs WT). PPAR-α mRNA expression was increased in WT, but not Nox2−/− mice (52%±11 vs −17%±11; p<0.05), while Nox2 mRNA expression remained elevated (1.33%±0.22 vs 0.69%±0.16 arbitrary units; p<0.05) in PPAR-α−/− versus WT mice after TAC. NADPH oxidase activity was significantly increased in TAC WT, but not PPAR-α−/− or Nox2−/− mice, although absolute levels in PPAR-α−/− remained elevated compared with WT sham. These data indicate co-dependence of PPAR-α and NADPH oxidases in the setting of pressure-overload LVH, although the underlying mechanisms are clearly complex.